The Rationality of Using Diclofenac in Outpatient Cases of Osteoarthritis of Mohammad Hoesin General Hospital Palembang Period January-March 2018 - Dara Prameswari; M. Totong Kamaluddin; Nita Parisa (HM Publisher, 2021)
Osteoarthritis (OA) is the most common disease in joints that affects people in their middle until late years. In Indonesia the prevalence of OA is relatively high and disturbs their daily activity. Diclofenac is one of the drug of choice in treating OA. To avoid multiple side effects from Diclofenac use, the usage must be in accordance to rationality indicators which are correct dose, correct frequency, and correct length of use. This study is aimed to know the rationality of Diclofenac use in Osteoarthritis outpatient cases at RSUP Mohammad Hoesin Palembang. This study is a descriptive observational with a cross-sectional approach to know the rationality of Diclofenac use in outpatient cases of osteoarthritis at RSUP Mohammad Hoesin Palembang. Samples were medical records of OA patients in outpatient setting from January to March 2018 which fulfilled the inclusion and exclusion criteria. Sampling technique used was total sampling. The amount of samples fulfilling the inclusion criteria were 201 patients, with the most were aged 46-65 years (60.2%), female (55.7%), and has a history of comorbidity which includes low back pain (22.8%). The result of this study shows pattern of Diclofenac use with dosage of 2 x 25mg (73.6%), length of use about <7 days (57.2%). In combination with other drugs there were no interaction to be found (84.4%), or synergistic interaction (8.5%) and antagonistic interaction (7.1%). The use of diclofenac in osteoarthritis cases at outpatient setting in RSUP Dr Mohammad Hoesin Palembang is rational and needs to be maintained.